The impact of broadband on jobs and the German economy - Raul L. Katz; Stephan Vaterlaus; Patrick Zenhäusern; Stephan Suter (Intereconomics, 2010)
This study calculates the impact of investment in broadband technology on German employment and economic output. Two sequential investment scenarios are analysed: the first one reflects the government's National Broadband Strategy that extends through 2014, and the second covers the ultra-broadband evolution from 2015 to 2020. The authors conclude that the required investment of close to 36 billion euros is justified by the substantial benefits that would be generated in terms of both additional jobs and GDP growth.
Keywords: 330